Internal marketing as a strategy to achieve sustainable competitive advantage: a case of the construction industry in Gauteng, South Africa - Gwinji, Wedzerai Andrew (My University, 2018)
Construction companies are aware of the importance of involving marketing in their management functions to adapt themselves not only to the continuous changes in the industry, but also to satisfy their clients’ demands, while being competitive and improving their business strategy. The construction industry is faced with increase in competition, globalisation and changing clients’ demands. This high level of competition, expectations and environmental impact has resulted in most companies finding more appropriate marketing approaches to satisfy their clients’ demands. Operating successfully in this environment requires having the right type of personnel in the right atmosphere and mind to create a sustainable competitive advantage. Therefore the current study is one of the few studies to investigate internal marketing as a strategy to achieve sustainable competitive advantage in construction industry in South Africa. In particular, this study sought to examine the effects of internal marketing dimensions internal communication, employee empowerment, inter-functional coordination, employee training and development and organisation commitment against sustainable competitive advantage.In total five hypotheses were postulated and in order to empirically test these hypotheses a data set of 260 collected from construction managers was used for the purpose. A structural equation modelling approach using AMOS 24 statistical software was used to empirically test the proposed five hypotheses using the collected data set. The analytical results implied that three of the proposed hypotheses were supported and two were not supported. Specifically, it appears that internal marketing has a positive impact on sustainable competitive advantages. Based on the current study findings, both academic and practical managerial contributions are made. On the academic front, new literature on a rarely researched subject of internal marketing as a strategy to achieve sustainable competitive advantage - in an often most neglected research context – construction industry context is generated. On the managerial front, recommendations on the possible strategies that can be adopted by marketing managers in the construction industry are provided based on the research findings. Finally, future research avenues are also proposed
A Masters dissertation submitted in fulfilment of the requirements for the degree of the Master of Commerce (Marketing) in the School of Economic and Business Science at the University of the Witwatersrand
Keywords: Service industries--Marketing; Marketing--Marketing; Communication in personnel management